PERILAKU PENGGUNAAN MINYAK GORENG SERTA PENGARUHNYA TERHADAP KEIKUTSERTAAN PROGRAM PENGUMPULAN MINYAK JELANTAH DI KOTA BOGOR - Firina, Firina; Retnaningsih, Retnaningsih; Johan, Irni Rahmayani (Jurnal Ilmu Keluarga dan Konsumen, 2010)
Specific objectives of the study are to: (1) determine cooking oil buying and using behavior; (2) analyze the influence of internal factors on the amount of cooking oil purchased and utilized; and (3) analyze the affecting factors on house wives’ participation on waste cooking oil collection program. Result of the study indicates that house wives’ purchase unbranded in plastic package cooking oil daily in small store around the house. The daily average of cooking oil is about 49,05 gram per capita. Most of them utilize cooking oil twice for frying. House wives’ have general knowledge of cooking oil, but unaware about wasted cooking oil collection program. Such factors as family size, wives employment status, and attitude toward cooking oil, significantly determine the buying and using behavior of cooking oil. In the meanful, family size knowledge about the program and attitude toward cooking oil gain influence house wives’ participation on wasted cooking oil collection program.